Transformasi Digital Bank Syariah di Indonesia: Studi Literatur - Alya Siti Hapsyah; Raden Nabilah Rizky Ramadhani; Dewi Nurhalisyah; Irfan Saefuloh (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2026)
Digital transformation has become one of the important strategies in developing the Islamic banking industry in Indonesia to improve efficiency, service quality, and competitiveness in the digital economy era. The development of technologies such as financial technology (fintech), mobile banking, open banking, artificial intelligence, and digital payment systems has encouraged changes in Islamic banking business models from conventional services toward a more innovative digital ecosystem. This study aims to analyze the development of digital transformation in Islamic banks in Indonesia, identify its benefits, challenges, and development strategies based on previous research findings. This research employs a qualitative approach using a literature review method by analyzing various scientific articles, regulatory reports, and institutional documents related to Islamic banking digitalization. The findings indicate that digital transformation has a positive impact on improving operational efficiency, accelerating services, expanding financial inclusion, and enhancing customer experience. However, the implementation of digitalization still faces several challenges, including cybersecurity risks, human resource readiness, digital literacy gaps, technological investment requirements, and the necessity to maintain sharia compliance principles. This study concludes that the success of digital transformation in Islamic banking depends not only on technological capabilities but also on strengthening governance, developing human resources, implementing adaptive regulations, and integrating digital innovation with Islamic values. A well-planned digital transformation strategy can strengthen the role of Islamic banks as modern, inclusive, and sustainable financial institutions.